A Huge Ancient Schwannoma of the Epiglottis. Issue 2 (March 2016) - Lee, Dong Hoon; Kim, Jo Heon; Yoon, Tae Mi; ,; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Abstract: Ancient schwannoma of the epiglottis is extremely rare. The authors report the first case of a patient with a huge ancient schwannoma of the epiglottis. Clinicians should consider the possibility that ancient schwannoma may originate in the epiglottis mimicking the other more frequently observed lesions.